2001
DOI: 10.2166/wst.2001.0360
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic treatment and biogas recovery for sago wastewater management using a fluidized bed reactor

Abstract: Starch manufacturing industrial units, such as sago mills, both at medium and large scale, suffer from inadequate treatment and disposal problems due to high concentration of suspended solid content present in the effluent. In order to investigate the viability of treatment of sago effluent, a laboratory scale study was conducted. The treatment of sago effluent was studied in a continuous flow anaerobic fluidized bed reactor. The start-up of the reactor was carried out using a mixture of digested supernatant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
3
13
2
Order By: Relevance
“…During the stepped increase of OLR, COD removal efficiencies were gradually increased. This was in general agreement with COD removal efficiencies were increased with time of operation (Saravanane et al, 2001). But, the reduction in HRT less than 12 h shown decreased trend in COD removal efficiencies in terms of both TCOD and SCOD.…”
Section: Start-up Of the Reactorsupporting
confidence: 88%
“…During the stepped increase of OLR, COD removal efficiencies were gradually increased. This was in general agreement with COD removal efficiencies were increased with time of operation (Saravanane et al, 2001). But, the reduction in HRT less than 12 h shown decreased trend in COD removal efficiencies in terms of both TCOD and SCOD.…”
Section: Start-up Of the Reactorsupporting
confidence: 88%
“…Khageshan and Govindan (1995) have reported that beyond an OLR of 11.6 kg COD/m 3 .day, gas production decreased during the treatment of synthetic Sago wastewater using anaerobic filter with basalt stone chips as filter medium. In contrast to the present observations, Saravanane et al, (2001) have reported a very high OLR of 60.5 kg COD/m 3 .day during the start up phase of treatment of synthetic Sago wastewater using a fluidized bed reactor. Interestingly, the efficiency of this reactor in terms of COD removal (82%) is lower than the value recorded during the present study (92%) during the start up.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, the efficiency of this reactor in terms of COD removal (82%) is lower than the value recorded during the present study (92%) during the start up. Further comparison between these two studies is not possible in the absence of data on HRT maintained by Saravanane et al, (2001). The anaerobic treatment of Sago wastewater using the Hybrid Upflow Anaerobic Sludge Blanket indicated promising results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tapioca tubers are the raw material and it is converted into commercial sago through indigenous technology. During the process, on an average from 30,000 to 40,000 litre of effluent is generated per tonne of sago processed and it takes about 10 days for the water to be let out of the factory as effluent (Belliappa 1991;Saravanane et al 2001). The release of high content of the organic load along with the effluent when stored, results in obnoxious odour, irritating colour, lower pH and higher BOD and COD (Ayyasamy et al 2002).…”
Section: Introductionmentioning
confidence: 99%